Maintaining Optimal Surgical Conditions With Low Insufflation Pressures is Possible With Deep Neuromuscular Blockade During Laparoscopic Colorectal Surgery: A Prospective, Randomized, Double-Blind, Parallel-Group Clinical Trial. Issue 9 (March 2016) - Kim, Myoung Hwa; Lee, Ki Young; Lee, Kang-Young; Min, Byung-Soh; Yoo, Young Chul
Abstract : Abstract: Carbon dioxide (CO2 ) absorption and increased intra-abdominal pressure can adversely affect perioperative physiology and postoperative recovery. Deep muscle relaxation is known to improve the surgical conditions during laparoscopic surgery. We aimed to compare the effects of deep and moderate neuromuscular block in laparoscopic colorectal surgery, including intra-abdominal pressure. In this prospective, double-blind, parallel-group trial, 72 adult patients undergoing laparoscopic colorectal surgery were randomized using an online randomization generator to achieve either moderate (1–2 train-of-four response, n = 36) or deep (1–2 post-tetanic count, n = 36) neuromuscular block by receiving a continuous infusion of rocuronium. Adjusted intra-abdominal pressure, which was titrated by a surgeon with maintaining the operative field during pneumoperitoneum, was recorded at 5-minute intervals. Perioperative hemodynamic parameters and postoperative outcomes were assessed. Six patients from the deep and 5 from the moderate neuromuscular block group were excluded, leaving 61 for analysis. The average adjusted IAP was lower in the deep compared to the moderate neuromuscular block group (9.3 vs 12 mm Hg, P < 0.001). The postoperative pain scores ( P < 0.001) and incidence of postoperative shoulder tip pain were lower, whereas gas passing time ( P = 0.002) and sips of water time ( P = 0.005) were shorter in the deep neuromuscular block than in the moderate neuromuscular block group. Deep neuromuscular blocking showed several benefits compared to conventional moderate neuromuscular block, including a greater intra-abdominal pressure lowering effect, whereas surgical conditions are maintained, less severe postoperative pain and faster bowel function recovery.